Acute effects of a vigorous-intensity warm-up on response suppression and decision-making of football referees - Albaladejo-García, C.; Caballero, C.; Asencio, P.; Moreno, F. J. (Journal of Sports Sciences, 2024)
This study investigates the acute effect of physical exercise simulating a standard pre-competitive warm-up on the response suppression and decision-making of football referees. Thirty-four referees (n = 17 - regional level; n = 17 - national level) participated in the study. A Stop-Signal Task (SST) and a decision-making video test were used to evaluate the referees` perceptual-cognitive functions. The findings revealed that the vigorous aerobic exercise acutely impacted basic cognitive functions, as indicated by decreased reaction time and decreased choice accuracy. However, higher-order cognitive functions such as response suppression and decision-making did not exhibit significant changes post-exercise. Based on these results, there is no evidence to suggest that a vigorous-intensity warm-up is likely to favour response suppression and decision-making factors in the initial phases of the game. National referees showed superior response suppression abilities (shorter stop-signal reaction times and lower probability of responding to the stop-signal) than regional referees, indicating that higher-level referees possess enhanced perceptual-cognitive skills, likely influenced by their experience. Further studies are required to determine whether these variables can be acutely improved through physical exercise. In this regard, our results suggest the need for alternative strategies in pre-competitive referee warm-ups if aiming to improve perceptual-cognitive skills in the initial phases of the game.